Molecular insights into the axon guidance molecules Sidestep and Beaten path - Heymann, Caroline; Paul, Christine; Huang, Na; Kinold, Jaqueline C.; Dietrich, Ann-Christin; Aberle, Hermann (Frontiers in Physiology, 2022)
The transmembrane protein Sidestep (Side) functions as a substrate-bound attractant for motor axons in Drosophila. Outgrowing motor axons recognize Side via Beaten path Ia (Beat) and migrate along Side-expressing tissues. Here, we report a structure-function analysis of these guidance molecules using a variety of mutant lines and transgenic constructs. Investigation of Side mutants shows that the exchange of a single amino acid (L241H) in the second immunoglobulin (Ig) domain disturbs Side function and subcellular localization. Overexpression of Side and Beat deletion constructs in S2 cells and muscles demonstrate that the first Ig domains of both proteins are necessary for their interaction. Furthermore, subcellular distributions of several Beat constructs identify functional domains and suggest a potential posttranslational processing step in ER compartments. In fact, fusing full-length Beat at both the N- and C-terminus with GFP and mCherry, respectively, shows that the N-terminal domain is transported to the plasma membrane and exposed on the cell surface, while the C-terminal domain accumulated in the nucleus. Taken together, these results give insights into the interaction of Side and Beat and imply that Beat might be subject to proteolytic cleavage during maturation.